Assessment of hygienic-sanitary status and implementation of an integral risk management program in butcher shops from Tafí Viejo city, Tucumán, Argentina - Moreno Mochi, Maria Paula (2024)
Meat and meat products promote the growth of pathogens such as Shiga toxin-producing Escherichia coli and Salmonella spp. In this work, an evaluation was carried out through risk quantification and microbiological analysis on ground beef and environmental surfaces in butcher shops, of Tafí Viejo city, Tucumán province. The study was carried out in three periods: period 1 (description of the health-status), period 2 (implementation of improvement actions) and period 3 (verification of success). Ground beef samples and environmental surfaces were analyzed in the previously described periods. The improvement actions in each butcher shop were implemented on the deviations detected in the first period. An increase of 35.7 % in low-risk butchers was observed. Microbial indicators in ground beef were significantly lower for total aerobic mesophilic microorganisms and Stapylococcus aureus, compared to the first period. In ground beef samples and environmental surfaces, the detection/isolation of STEC non-O157, presented a 100 % decrease in the verification period. The detection of Salmonella spp. showed a reduction of 14.3 % only on ground beef samples. This study confirms that the implementation of a risk management program in butcher shops would reduce contamination of ground beef and the environment with pathogens.